Considerations on the surgical treatment of stomach cancer - Carrillo Maurtua, Luis (1955)
Stomach resection is currently the only logical solution in the treatment of adenocarcinoma of the stomach. The extension of this visceral resection is logged in to the extent of cancer visceral. In some cases it is necessary to extend the esophagus; Total gastrectomy. In other cases it is necessary to remove organs or segments órghanos invalid; Extended gastrectomy.